A COMPANY VALUE IMPACT OF CAPITAL STRUCTURE, SALES GROWTH AND COMPANY SIZE - Hertina, Dede; Sianturi, Taruli Br; Imanudin, Permana (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine the effect of capital structure, sales growth, and firm size on firm value in automotive and component sub-sector companies listed on the Indonesian stock exchange for the 2014-2018 period. The method used in this research is descriptive method. The population in this study are companies in the automotive and component sub-sector listed on the Indonesia Stock Exchange for the period 2014-2018 as many as 13 companies. The results of the study simultaneously state that capital structure, sales growth, and company size have a positive and significant effect on firm value in the automotive and component industry sub-sector companies listed on the Indonesia Stock Exchange for the 2014-2018 period. While the results of the study partially state that capital structure has a positive and significant effect on firm value, sales growth has no effect on firm value and firm size has a negative effect on firm value in automotive and component industry sub-sector companies listed on the Indonesia Stock Exchange for the 2014- 2018 period.